Do Nonprofits Treat Their Employees Differently? Incentive Pay and Health Benefits. Issue 3 (20th December 2013) - Chen, Xinxiang; Ren, Ting; Knoke, David
Abstract We examine how nonprofit, public, and for‐profit establishments vary in the provision of health benefits and insurance and performance‐based incentives using the 2002 National Organization Survey of establishments in the United States. We found that in comparison to for‐profit firms, both nonprofit and public organizations are less likely to use performance‐based incentives, although they provide their employees with better health benefits and insurance. Sectoral differences in the provision of health benefits and insurance and use of performance‐based incentives persist after controlling for correlates of sector that predict these outcomes, including establishment size, independence of establishment, market competition, establishment age, and unionization. We also found trade‐offs between the provision of health benefits and insurance and use of performance‐based incentives. Our results are generally consistent with the prediction from agency theory and also consistent with a view that public and nonprofit organizations are more concerned with the well‐being of their employees.